Kinetics and Mechanism of Gold Dendrite Electroformation on C(0001) : Activation Energy for Gold Adatom Surface Diffusion - Martín, H. (1999)
Au electrodeposition on C(0001) from aqueous solutions with different concentrations of AuCl3·HCl, at a constant ionic mass transport rate (jL), in the temperature range 275 ≤ T ≤ 313 K, results in the initial formation of nanometer-sized Au islands consisting of a central core and symmetrically distributed branches with the island fractal dimension Df = 1.6. For all values of T, the time dependence of the Au island radius fulfills a r ∝ tn relationship with n = 0.25 ± 0.05. At constant T, the density of Au islands (Ns) increases according to Ns ∝ jLX with X = 0.69 ± 0.03. At constant jL, the value of Ns decreases as T is increased, following an Arrhenius-type relationship. Kinetic data are consistent with a growth mechanism involving surface diffusion of Au adatoms from the island core towards branch tips. From the dependence of Ns on T at constant jL, the activation energy for Au adatom surface diffusion results in Ea* ≈ 11 Kcal/mol. This figure is slightly smaller than Ea* ≈ 14 Kcal/mol that has been reported for Au atom surface diffusion in Cl--ion free acid solutions.